Packaging and storage condition affect the physicochemical properties of red raspberries (Rubus idaeus L., cv. Erika). (March 2019) - Giuffrè, A.M.; Louadj, L.; Rizzo, P.; Poiana, M.; Sicari, V.
Abstract: Packaging material and the storage temperature on red raspberries ( Rubus idaeus L.) were studied in this paper. Raspberries were stored following their harvesting in different conditions: in the fridge at 1 °C and in the freezer at −20 °C, using different packaging materials: two Nanoactive films, Nanoactive A (NA) and Nanoactive B (NB), a biaxially oriented polyethylene terephthalate (PET) film and some other fruits were stored without any film (WF). Biometrics, color, titratable acidity, soluble solid content and moisture, were determined during storage. A loss of weight (24.87%) was found during storage at room temperature from 5.02 g to 4.02 g in two days. During the freezer storage was found a significant average higher Solid Soluble Content (9.44 °Brix) in PET, a significant higher Titratable acidity (2.08%) in WF, and no significant differences between different packaging for Moisture content. The O2 and CO2 concentrations were measured daily in the refrigerated fruits and the O2 concentration on the 7th day was 5.0% (NA), 19.8% (NB) and 17.1 (PET). CO2 percentage increased significantly during storage in the NA package from 9.6 (1st day) to 20.3 (14th day), whereas an inverse trend was found in the NB package from 4.4 (1st day) to 1.0 (4th day). Highlights: Red raspberries without refrigeration show a very short shelf-life, maximum one day. Nanoactive films maintain valuable physical-chemical characteristics during storage in the fridge. Nanoactive A have shown the highest shelf-life (14 days). Freezing maintain valuable physical-chemical characteristics of raspberry.